Law, Violence, Music, and Decolonising the Coronation Ceremony - Edwin Bikundo (Law Text Culture, 2023)
Whereas both law and music have provided justification for specific uses of violence as a necessary evil, that overlap between two is seldom considered beyond relatively obscure aspects of Ernst Kantorowicz’s work and Giorgio Agamben’s allusions to that work. Which is to say that although law and music have provided means explaining the role of violence (a lay theodicy) this remains unexplored and under theorised. Musicality with its cadences, both tones and rhythms, is uniquely placed to consciously marshal the unconscious impersonal centripetal-centrifugal forces that simultaneously promise to bring society together while threatening to tear it apart. This moreover is all done sub rationally which is to say it takes the place of any transcendent logical legitimation of the society under ritual formation. The paper argues that the common relation combining music, law and violence is that each singly and together can be directed to either aggregate or disaggregate - ceremoniously, the body politic. Coronation ceremonies centring music in the installation of the monarch are no exception to this, instead being in their own way exemplary of those relations and that process.